Oil and Small Open Macroeconomy: A case of Korea - Lee, Junhee; Song, Joonhyuk (Global economic review, 2012)
The world oil price has risen significantly since the late 1990s and reached a record high in 2008. The recent oil price hike raises concerns regarding the possible negative effects of the rising oil price on the economy as in the 1970s. We investigate the effects of the oil price hike on the Korean economy using a Bayesian dynamic stochastic general equilibrium (DGSE) model. We explicitly model the small open economy nature of the Korean economy and its oil usage and estimate the constructed model within a unified Bayesian framework. We also examine possible changes in the effects of world oil shocks on the Korean economy using counterfactual simulations. We find the adverse effects of world oil shocks as well as their importance in Korean business cycles have diminished due to reductions in the relative usage of crude oil in the economy, while world oil shocks themselves have changed relatively little over time.